Analisa Kelayakan Usaha Budidaya Teripang (Holothuroidea) di Distrik Samate, Kabupaten Raja Ampat - Ratna Ratna; Amir M Suruwaky (Jurnal Airaha, 2016)
The cultivation of sea cucumbers in Samate District, the Raja Ampat is highly potential due to sufficient conditions of waters which is protected from the influence of currents, waves and a storm. The purpose of this study was to analyze the feasibility of sea cucumber cultivation in Samate districtRaja Ampat, referring to the prospect of future development. Data was collected in Samate district, Raja Ampat in November 2015 - February 2016. Samples were taken by purposive sampling method from representatives of farmers with consideration of the same level of diversity of sea cucumber cultivation area. Data analysis was performed by using financial feasibility analysis of sea cucumber cultivation with calculation of profit / loss, R-C ratio and BEP. The results showed that the earned profits in a year is amounted to Rp 25.388.000, while the value of B / C (Benefit Cost Ratio) is 3.25 or B / C > 1 which indicates that the business is feasible to be developed. BEP analysis is amounted of 4.6 kg, with the price of Rp 307.500 / kg, which means that the minimum production should be 4.6 kg at a price of Rp 307.500 /kg to achieve the capital return conditions.